In vivo micro-Raman spectroscopy from an arbitrary-shaped region of interest under simultaneous reflectance confocal imaging guidance - Zhenguo Wu; Liwei Jiang; Jianhua Zhao; Harvey Lui; Haishan Zeng (APL Photonics)
Confocal Raman spectroscopy (CRS) has been widely used for noninvasive biochemical analysis of biological tissue in vivo. Currently, reflectance confocal microscopy (RCM) has been integrated with CRS as visual guidance for a square-/rectangular-shaped region of interest or a point of interest micro-Raman measurement. However, biological structures often have various morphologies; it is highly desirable to acquire a representative Raman spectrum from and only from the area that covers the whole target biological micro-structure. To achieve this goal, we developed a method to acquire Raman spectrum from a region of interest with any (arbitrary) shape under simultaneous RCM imaging guidance.